Gap Assessment of Hotel Industry and Academia Interface with reference to the State of Punjab (India) - Gaurav Bathla, Varinder Singh Rana, Manjinder Singh Jatana (International Journal of Advanced Science and Technology, 2020)
Academia is the merchant for providing skilled manpower as per the requirements to the Industry. Henceforth, it is vital that industry gives constant feedback to the institutions so as to empower the students to with latest knowledge and during the course of education. This research paper is based upon quantitative research and aims to access gap between hotel industry and academia interface. This study largely deals with hotel management where all knowledge, skills, attitude and ability is seen as essential for the bright future in hospitality industry. Questionnaire as the main tool was used to gather the data from the hotel management faculty members and industry managers on the various hotel industry and academia interface statements developed for the study.